Exploring the knowledge and attitudes towards metabolic dysfunction associated fatty liver disease (MAFLD): Validation and correlations of MAFLD-knowledge questionnaire and MAFLD-attitude questionnaire - Samah Al Tawil; Mohamad Abdelkhalik; Adam El Fouani; Nour Allakiss; Lama Mattar; Wissam H. Faour; Rajaa Chatila (Heliyon)
Background: Metabolic dysfunction associated fatty liver disease (MAFLD) is a highly prevalent non-communicable disease whose prevalence is reaching pandemic proportions. Its implications constitute a major public health concern. To date, no validated tool measures knowledge and attitudes towards MAFLD in young adults in the Middle East and North Africa region. Objective: To establish and validate questionnaires that measure knowledge and attitudes towards MAFLD. Methods: MAFLD-Knowledge Questionnaire (KQ) and MAFLD-Attitudes Questionnaire (AQ) were developed by disease content experts and piloted on a group of 20 students. The questionnaire was next administered to 406 university students aged 18–24 years. The dimensionality of the instrument was tested using exploratory factor analysis and consistency with Cronbach's alpha. Finally, known-group validity was assessed by comparing the knowledge and attitudes of those with poor versus good knowledge. Results: For the knowledge questionnaire, 28 out of 32 questions had good loading and were thus included. Based on Exploratory Factor Analysis (EFA), there were 4 domains with Kaiser–Meyer–Olkin (KMO) 0.95 and Bartlett test with P < 0.001, with very good internal consistency (Cronbach's alpha 0.88). For the attitudes questionnaire, 17 items were extracted all with adequate loading. EFA revealed 3 domains with KMO of 0.95 and very good internal consistency (Cronbach's alpha 0.81). Known group validity showed a significant difference between the attitudes of subjects with poor and moderate knowledge and poor and high knowledge scores but not between moderate and high knowledge scores. Conclusion: We developed and validated two questionnaires, one for the assessment of knowledge and the other for attitudes towards MAFLD in young adults. Further studies are needed to confirm dimensionality and reproducibility in different populations and age groups.